1992
DOI: 10.3171/jns.1992.76.2.0207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of head elevation on intracranial pressure, cerebral perfusion pressure, and cerebral blood flow in head-injured patients

Abstract: The traditional practice of elevating the head in order to lower intracranial pressure (ICP) in head-injured patients has been challenged in recent years. Some investigators argue that patients with intracranial hypertension should be placed in a horizontal position, the rationale being that this will increase the cerebral perfusion pressure (CPP) and thereby improve cerebral blood flow (CBF). However, ICP is generally significantly higher when the patient is in the horizontal position. This study was undertak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
152
0
16

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(171 citation statements)
references
References 18 publications
3
152
0
16
Order By: Relevance
“…However, 13 patients showed lower ICPPA values at 0°position. The 30°head-up position is often used intuitively, and it was shown to be associated with low ICP and improved cerebral oxygenation in several studies [13,16,23,29,33,34,40,53]. However, all these studies also showed a considerable individual variability in terms of the optimum level of head elevation.…”
Section: Head Elevation and Cerebral Hemodynamicsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, 13 patients showed lower ICPPA values at 0°position. The 30°head-up position is often used intuitively, and it was shown to be associated with low ICP and improved cerebral oxygenation in several studies [13,16,23,29,33,34,40,53]. However, all these studies also showed a considerable individual variability in terms of the optimum level of head elevation.…”
Section: Head Elevation and Cerebral Hemodynamicsmentioning
confidence: 95%
“…The results of a study by Feldman et al [16] suggested that head-injured patients with raised ICP should be positioned with the head elevated to 30°. This will produce a reduction of the ICP without a significant decrease in cerebral blood flow (CBF) or CPP in the majority of measured patients.…”
Section: Head Elevation and Cerebral Hemodynamicsmentioning
confidence: 99%
“…136 It has also been reported that visually defected rats may regain some degree of visual acuity after exposure to an EE. 17 The prophylactic effects of EE exposure prior to undergoing a TBI has also shown positive results. 137 Spinal cord-injured rats also display functional recovery once exposed to an EE.…”
Section: Neurorestorationmentioning
confidence: 88%
“…10,11 Head elevation augments venous drainage of the head and reduces ICP in the ICU setting. [4][5][6][7][8][9] Enhanced venous drainage induced by head elevation may off-set the effect of impaired venous drainage caused by head rotation resulting in a reduced risk for intracranial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Head elevation lowers ICP 2,3 and reduces intracranial hypertension secondary to trauma and intracranial hemorrhage in the ICU setting. [4][5][6][7][8][9] Head rotation increases ICP by impeding venous drainage of the head in adults 10,11 and infants. 1 3 The increase in ICP associated with head rotation in infants was reduced by concomitant head elevation.…”
mentioning
confidence: 99%